Bernhard Bolzano und die Zensur - Grzywacz, Małgorzata (Studia Germanica Posnaniensia, 2018)
Austria between 1815-1848, i.e. before it became a great power, remained under the overwhelming influence of Chancellor K. Metternich and his policy towards various liberal and national movements. This was to be reflected in the so called Karlsbad Settlments of 1820 (Karlsbader Beschlüsse), the consequence of wich was the establishment of a police state and severe censorship that would resort even to the confiscation of manuscripts. Bernard Balzano's views concerning the state, the nation and religion challenged Metternich's regime. He was professor of philosophy an an academic priest in Prague and a civil servant at the same time. He popularized his liberal views in church. His sermons against totalitarianism demanded a constitution and equality of rights for different nations within the monarchy. Such views were rather inconvenient for the establishment since they might constitute a hotbed of rebellion. Therefore, in 1819 Bolzano was dismissed as a professor. Church community, who also found his opinions inconvenient, put him a his first serious trial, which however, was not able to make Bolzano recant his beliefs. From 1820 onwards Bolzano was subjekt to double censorship, namely censorship performed both by the state and the church. This censorship continued till the philosopher's death in 1848. All texts that Bolzano had published in the course of his life, came out in neighbouring Bavaria, governed in more liberal way. Being doomed by the double censorship to scholary non-existence, Balzano's ideals and views did not stand the chance to be easily reached by the posterity and this, in turn, impeded the reception of his thought, even in the German speaking countries.